Teachers Strategies in Handling Bullying Cases in Elementary Schools: A Systematic Literature Review - Sri Lestari; Sumarno (Universitas Pendidikan Ganesha, 2026)
Bullying in primary schools remains a difficult issue to address consistently because it is often perceived as part of students' social dynamics rather than a pedagogical problem that requires structured intervention. This condition causes negative impacts on students' emotional, social, and psychological development to recur without a comprehensive handling strategy. This study aims to analyze and synthesize teachers' strategies in dealing with bullying in elementary schools based on previous research findings. The approach used was a Systematic Literature Review of ten articles that met the inclusion criteria and were published in the 2020-2024 timeframe. The analysis process was carried out thematically through the stages of data extraction, coding, categorization of findings, and concept synthesis. The results of the study show that teacher strategies include a preventive approach through strengthening character education, direct intervention in the form of mediation and student assistance, and collaboration between teachers, schools and parents. The findings also confirm that teacher competence in early detection, consistency of school policies, and support from the social environment determine the success of the handling. The contribution of this research lies in systematically mapping the variations in teachers' strategies and their implementation barriers in the context of primary education. The practical implications of the research results indicate that strengthening teachers' professional capacity and developing sustainable anti-bullying programs need to be placed as an integral part of primary school policies.